2022
DOI: 10.1038/s41420-022-01000-w
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: MIR600HG sponges miR-125a-5p to regulate glycometabolism and cisplatin resistance of oral squamous cell carcinoma cells via mediating RNF44

Abstract: There is increasing evidence that dysregulated long non-coding RNA (lncRNA) is implicated in tumorigenesis and progression. We aim to explore the role of lncRNA MIR600HG in glycometabolism and cisplatin (DDP) resistance of oral squamous cell carcinoma (OSCC) cells via regulating microRNA-125a-5p (miR-125a-5p) and RING finger 44 (RNF44). Expression of MIR600HG, miR-125a-5p, and RNF44 in OSCC clinical samples, cell lines, and DDP-resistant OSCC cells (SCC-9/DDP) was determined. In SCC-9 cells, proliferation, IC5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…In several human cancer types, including medulloblastoma, and lung, ovarian and breast cancer, the expression of miR125a-5p is downregulated ( 128 ). In oral squamous cell carcinoma, miR-125a-5p expression is also markedly downregulated ( 129 ). These findings indicate that miR-125a-5p may function as a tumor suppressor.…”
Section: Mirnas In Accmentioning
confidence: 99%
“…In several human cancer types, including medulloblastoma, and lung, ovarian and breast cancer, the expression of miR125a-5p is downregulated ( 128 ). In oral squamous cell carcinoma, miR-125a-5p expression is also markedly downregulated ( 129 ). These findings indicate that miR-125a-5p may function as a tumor suppressor.…”
Section: Mirnas In Accmentioning
confidence: 99%
“…However, recent studies have confirmed that lncRNAs are involved in processes such as X chromosome silencing, chromosomal and genome modification, transcriptional activation, transcriptional perturbation, and nuclear transport, and play important regulatory roles in many aspects of tumor pathology. At the same time, it can also play a role in tumor diagnosis and treatment by promoting or inhibiting the development of cancer [7,8]. A previous study reported that LncRNAs play a role in thyroid cancer by targeting microRNA (MiRNA) blockade [9].…”
Section: Introductionmentioning
confidence: 99%